Micro, Small and Medium-sized Enterprises in the Digital Economy: Barriers to Digitalisation - Węgrzyn, Grażyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2025)
Objective: To identify the barriers to digitalisation micro, small and medium-sized enterprises (SME) in Poland face, using enterprises in Dolnośląskie voivodeship as an example. Research Design & Methods: A review of the subject literature on the essence, level and importance of the digitalisation of enterprises, as well as on the limitations in the use of digital technologies by SMEs. The review is complemented by empirical research conducted in June and July 2023 on a sample of 50 enterprises. The research was preceded by field observation. A questionnaire was administered in electronic (Microsoft Forms) and paper form among clients of an accounting office in the Dolnośląskie voivodeship. Findings: The results confirm that the level of digitalisation among micro, small and medium-sized enterprises in Poland is low. The owners of enterprises point to a range of barriers that discourage them from implementing digital solutions. The research showed that, among the micro, small, and medium-sized enterprises surveyed, the most frequent barriers to implementing digital solutions were a successfully functioning business, a lack of knowledge on available digital solutions, and a lack of clarity regarding the benefits that such solutions may bring. Meanwhile, firms that have already begun digital transformation indicated a range of barriers to further implementation of digital solutions, including a lack of suitable competences, high investment costs, and concerns about leaving traces in the digital world and being exposed to various types of inspections. Implications / Recommendations: There is a need for education and support of digital competences, as well as to increase awareness among the owners of small firms as to the benefits digitalisation promises. At the same time, data and privacy must be protected in order to encourage entrepreneurs to safely implement digital solutions. Contribution: The research conclusions fill a research gap and can be used by both practitioners and theoreticians. Understanding both the level of digitalisation in SMEs and the barriers hindering the use of digital technologies should help the field develop.